Metabolomics and flavoromics analysis of chemical constituent changes during roasting of germinated Sacha inchi (Plukenetia volubilis L.) - Kannika Keawkim; Kriskamol Na Jom (Food Chemistry: X, 2022)
This study examined the changes in metabolites together with the flavor profiles of germinated Sacha inchi seeds during roasting by using gas chromatography. The results indicated that roasting partially increased the browning index, amino acid levels, total phenolic content, and antioxidant capacity, but slightly decreased the levels of reducing sugars. Oxidized and rancid compounds were significantly decreased at a 180 °C roasting temperature. Pyrazine, furan, and pyrrole were Maillard reaction products that were increased at 180 °C of roasting. Roasting at 145 °C for 45 min after germination for 4 days was determined to be the optimal conditions for roasting germinated Sacha inchi seeds, which reduced the off-flavor and burned taste. The roasted germinated Sacha inchi seed contains higher amino acids than raw seed, which could be used as an alternative source for food products and supplements. In addition, the roasted germinated seeds at 4 days were recommended for food applications.